2023
DOI: 10.1186/s12903-023-02822-5
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Molecular mechanism and diagnostic marker investigation of endoplasmic reticulum stress on periodontitis

Abstract: Purpose The aim of this study was to reveal the biological function of endoplasmic reticulum stress (ERS)-related genes (ERSGs) in periodontitis, and provide potential ERS diagnostic markers for clinical therapy of periodontitis. Methods The differentially expressed ERSGs (DE-ERSGs) were reveled based on periodontitis-related microarray dataset in Gene Expression Omnibus (GEO) database and 295 ERS in previous study, followed by a protein–protein in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…Future analysis of the effect of reducing reagents, including DTT, on the association of EDEM2 and TXNDC11 and the stability of unbound EDEM2 is needed. Recently, high expression of EDEM2 in several cancer cell lines, including glioma, 27,28,29) has been reported, although it is unclear whether high EDEM2 expression is related to cancer cell proliferation and poor prognosis via ERAD enhancement. Further investigations of this finding will contribute not only to the regulation of the basic molecular mechanisms of ERAD but also to tumor control.…”
Section: Resultsmentioning
confidence: 99%
“…Future analysis of the effect of reducing reagents, including DTT, on the association of EDEM2 and TXNDC11 and the stability of unbound EDEM2 is needed. Recently, high expression of EDEM2 in several cancer cell lines, including glioma, 27,28,29) has been reported, although it is unclear whether high EDEM2 expression is related to cancer cell proliferation and poor prognosis via ERAD enhancement. Further investigations of this finding will contribute not only to the regulation of the basic molecular mechanisms of ERAD but also to tumor control.…”
Section: Resultsmentioning
confidence: 99%
“…In the present study, we found the expression of GRP78 and CHOP to be upregulated when cells were exposed to Pg‐LPS. The upregulated expression levels of endoplasmic reticulum stress‐related genes included GRP78, PERK, ATF4, and CHOP, further indicating that endoplasmic reticulum stress might act as a promising therapeutic target against periodontitis [25, 26]. Up‐regulation of these factors in periodontitis lesions indicates that periodontal infection may trigger an apoptotic response and that apoptosis plays an important role in periodontitis [20].…”
Section: Discussionmentioning
confidence: 99%
“…1. Weighted linear regression model was used to determine the p value of the continuous variable, weighted chi-square test categorical variable 30 . Under the bilateral test, p < 0.05 is considered statistically signi cant.…”
Section: Discussionmentioning
confidence: 99%